2023
DOI: 10.1021/acsapm.3c01381
|View full text |Cite
|
Sign up to set email alerts
|

Transparent and Environmentally Adaptive Semi-interpenetrating Network Hydrogels for Electromagnetic Interference Shielding

Shuaiwei Yuan,
Tianwen Dai,
Xinyue Jiang
et al.

Abstract: In this work, by constructing a semi-interpenetrating network (semi-IPN) structure, one type of transparent and environmentally adaptive polyacrylamide (PAM)/poly(vinyl alcohol) (PVA)/ LiCl semi-IPN hydrogel with effective electromagnetic interference (EMI) shielding performance and good mechanical properties was successfully fabricated. The addition of lithium chloride effectively enhanced the antidehydration and antifreezing performance of PAM/ PVA hydrogels. As the initial LiCl concentration was 12 mol/L, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…The total shielding efficiency (SE) was measured using various scattering parameters (S 11 , S 12 , S 21 , S 22 ) and equation 7 of the Supporting Information, which measures the attenuation of electromagnetic waves passing through the hydrogel . At a frequency of 20 GHz, the AM 20 -Ca 2+ hydrogel displayed a total shielding efficiency (SE) of ∼35 dB (Figure A), which is far exceeding the industrial standard of 20 dB. This value also surpassed that of many other conducting filler-based elastomeric and hydrogel materials used for electromagnetic interference (EMI) shielding applications , , (Table S4). This exceptional EMI shielding ability of the AM 20 -Ca 2+ hydrogel may be attributed to three key factors: high water content (∼74%), a porous network, and adequate ionic conductivity.…”
Section: Resultsmentioning
confidence: 96%
“…The total shielding efficiency (SE) was measured using various scattering parameters (S 11 , S 12 , S 21 , S 22 ) and equation 7 of the Supporting Information, which measures the attenuation of electromagnetic waves passing through the hydrogel . At a frequency of 20 GHz, the AM 20 -Ca 2+ hydrogel displayed a total shielding efficiency (SE) of ∼35 dB (Figure A), which is far exceeding the industrial standard of 20 dB. This value also surpassed that of many other conducting filler-based elastomeric and hydrogel materials used for electromagnetic interference (EMI) shielding applications , , (Table S4). This exceptional EMI shielding ability of the AM 20 -Ca 2+ hydrogel may be attributed to three key factors: high water content (∼74%), a porous network, and adequate ionic conductivity.…”
Section: Resultsmentioning
confidence: 96%
“…25 Jia et al 26 prepared CA/AgNW/PU film with a high optical transmittance of 92% and achieved an EMI SE of 20.7 dB. Yuan et al 27 prepared a PAM–PVA–LiCl hydrogel, which showed absorption dominant EMI shielding performance beyond 35.6 dB. Zhou et al 28 prepared a PAM–PVA–GO–LiCl composite hydrogel that exhibited superior anti-dehydration and electromagnetic shielding (EMI) capabilities exceeding 37.2 dB.…”
Section: Introductionmentioning
confidence: 99%